The Influence of Rewards, Job Satisfaction, Organizational Culture, and Employee Engagement on Employee Retention Rates at Karunia Damai Sejati (KDS) Department Store Genteng - Ryamustika, Andiyan; Winahyu, Pawestri; Rusdiyanto (Ilomata International Journal of Management, 2025)
Employee retention is one of the main challenges in human resource management, especially in the retail sector which has a high turnover rate. This research aims to analyze the influence of Rewards, Job Satisfaction, Organizational Culture, and Employee Engagement on employee retention levels at Karunia Damai Sejati (KDS) Department Store Genteng. This research uses quantitative methods with a causal approach. The research population was all 65 KDS employees, using a total sampling technique. Data was collected through questionnaires and analyzed using multiple linear regression. The research results show that Rewards and Job Satisfaction have a significant influence on employee retention, with ttt values of 2,764 (p=0.008) and 3,834 (p=0.000), respectively. However, Organizational Culture (t=0.539, p=0.592) and Employee Engagement (t=1.442, p=0.155) did not have a partially significant effect. Simultaneously, these four independent variables have a significant effect on employee retention (F=30.527, p=0.000), with an R2 value of 0.671, indicating that 67.1% of the variation in employee retention can be explained by these variables. This research emphasizes the importance of Rewards and Job Satisfaction as priorities in strategies to increase employee retention.